Investing in Residential Real Estate : A Smart Decision? - Kirkerud, Johanne Olimb; Tyll, Ladislav; Srivastava, Mohit; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2018)
My goal for this thesis is to provide a deeper understanding of the housing market in Oslo, by comprehending why and how the prices fluctuates the way they do. In order to do so, I have analyzed the housing prices over the past 18 years. Furthermore, I have performed a regression analysis to understand the main influencing factors affecting the housing prices. I have then calculated the price-to-rent ratio as well as using the Hodrick-Prescott filter to detect if there are any “bubble tendencies” in the housing market in Oslo. Based on this I have been able to understand the underlying factors and whether or not it is a smart decision, investing in residential real estate in any of the specified areas.
Vedoucí práce: Ladislav Tyll
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses